2017
DOI: 10.18632/oncotarget.17606
|View full text |Cite
|
Sign up to set email alerts
|

Eight potential biomarkers for distinguishing between lung adenocarcinoma and squamous cell carcinoma

Abstract: Lung adenocarcinoma (LADC) and squamous cell carcinoma (LSCC) are the most common non-small cell lung cancer histological phenotypes. Accurate diagnosis distinguishing between these two lung cancer types has clinical significance. For this study, we analyzed four Gene Expression Omnibus (GEO) datasets (GSE28571, GSE37745, GSE43580, and GSE50081). We then imported the datasets into the Gene-Cloud of Biotechnology Information online platform to identify genes differentially expressed in LADC and LSCC. We identif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
41
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 63 publications
(48 citation statements)
references
References 62 publications
7
41
0
Order By: Relevance
“…30). Importantly, KRT5, KRT6A, KRT6B, and DSG3 were recently highlighted through ROC curves as biomarkers to differentiate lung adenocarcinoma from lung squamous cell cancer (31). Indeed, our analysis showed that KRT5, KRT6A, KRT6B, and DSG3 were highly expressed in LuCaP 173.2 squamous pearl cells compared with surrounding DNPC tissue ( Figure 5B).…”
Section: Resultsmentioning
confidence: 51%
“…30). Importantly, KRT5, KRT6A, KRT6B, and DSG3 were recently highlighted through ROC curves as biomarkers to differentiate lung adenocarcinoma from lung squamous cell cancer (31). Indeed, our analysis showed that KRT5, KRT6A, KRT6B, and DSG3 were highly expressed in LuCaP 173.2 squamous pearl cells compared with surrounding DNPC tissue ( Figure 5B).…”
Section: Resultsmentioning
confidence: 51%
“…Among the most significant shared genes that are associated with COVID-19 are KRT6B and TNFAIP3. Keratin 6B (KRT6B) is a type II cytokeratin, which is an important biomarker for lung adenocarcinoma (Xiao et al 2017). These genes are known as a virus-induced host factors that control the recruitment of Tcells and correlates to chronic virus infections ).…”
Section: Given the Important Association Between Heparin-binding Go Amentioning
confidence: 99%
“…Likewise, the keratin 6B (KRT6B) gene encodes for a type II keratin that is normally present in mammalian epithelial cells and is rapidly induced in human keratinocytes after skin wounding [26]. KRT6B has been identified as a potential biomarker for differentiating between lung adenocarcinoma and lung squamous cell carcinoma, and its increased expression is associated with lower disease-free survival rates in young breast cancer patients [27,28]. Mutations in the KRT6B gene result in an autosomal dominant skin disorder known as pachyonychia congenita, which involves plantar keratoderma and pain alongside thickened toenails [29].…”
Section: Discussionmentioning
confidence: 99%